2011
DOI: 10.1017/s0007114511001085
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial peptides derived from caprine whey proteins, by digestion with human gastrointestinal juice

Abstract: Peptides in caprine whey were identified after in vitro digestion with human gastrointestinal enzymes in order to determine their antibacterial effect. The digestion was performed in two continuing steps using human gastric juice (pH 2·5) and human duodenal juice (pH 8) at 378C. After digestion the hydrolysate was fractionated and 106 peptides were identified. From these results, twenty-two peptides, located in the protein molecules, were synthesised and antibacterial activity examined. Strong activity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 42 publications
2
39
0
1
Order By: Relevance
“…It is interesting to note that the protein bands corresponding to the apparent molecular mass of actin remained nearly intact for all hydrolysates, suggesting that this subunit is rather stable in the part of the protein and hindered access from gastric juices and pepsin. Similar relations were reported by Eriksen et al [42] who compared the course of in vitro hydrolysis of milk proteins with pepsin with hydrolysis with human gastric juices.…”
Section: Resultssupporting
confidence: 86%
“…It is interesting to note that the protein bands corresponding to the apparent molecular mass of actin remained nearly intact for all hydrolysates, suggesting that this subunit is rather stable in the part of the protein and hindered access from gastric juices and pepsin. Similar relations were reported by Eriksen et al [42] who compared the course of in vitro hydrolysis of milk proteins with pepsin with hydrolysis with human gastric juices.…”
Section: Resultssupporting
confidence: 86%
“…12,13 The results of studies with human digestive enzymes (ex vivo digestion) are closer to the results from in vivo rather than in vitro experiments. These studies have mimicked or approximated the physiological conditions of the human body.…”
Section: Introductionmentioning
confidence: 57%
“…26 Liberation of the three antibacterial peptides from cheese whey by three enzymes at various pHs was examined. LC-MS/MS analysis revealed that -lactoglobulin f(92-103) and lactoferrin f (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) were generated by pepsin-mediated digestion at pH 2.5 and 3.0, whereas -lactoglobulin f (14)(15)(16)(17)(18)(19)(20)(21)(22) was generated only at pH 2.5. In contrast, calf rennet digestion generated the all three peptides at a wider pH range (2.5-3.5) ( Fig.…”
Section: Identification Of Antibacterial Peptides In Calf Rennet Digementioning
confidence: 99%